Análisis socioeconómico del mercado de plantas ornamentales del Cantón Quevedo, Provincia de los Ríos. - Reyes Quijije, Shirley Soraya (2011)
Ornamental plants each day have greater importance within the landscaping and gardening green areas public or private. These plant species contribute with their ornamental character to beautify and improve the environment of the environment, achieving a leisure place for the man in your everyday life. The population has always expressed its interest in acquiring a diversity of species, either by size, color and shape of their leaves, so the market currently in production and consumption is in constant development, although there is very little existing bibliographic information. In this respect, the objective of this research work is to analyze the problems surrounding the production, marketing of ornamental plants and its impact on the agricultural sector, as well as, the importance in the socio-economic development of the canton Quevedo and the region. An investigation was conducted of descriptive character that systematically analyzed and interpreted the information gathered. The results reported that the population acquires by the satisfaction that you provide to decorate your home or garden, and prefer the palms, shrubs and ferns ixoras. The 48% of the surveyed population is devoted to the production and marketing of ornamental plants. The marketing is done in nurseries (22%), city tours (48%). Plants are more required thepalms (35%), shrubs (17%) and ferns (13%), by the color and shape of their leaves, and the size of the plant. The income received do not cover their basic needs so you don't have improved their quality of life and have not contributed to the agricultural development of the canton Quevedo, being necessary to carry out training programs, business creation and access to credit viable with low interest.